Illustrations and Studies in Neotropical Orchids. 2. A note on Pleurothallis luctuosa (Orchidaceae: Pleurothallidinae), with a new species - Pupulin, Franco (2010)
The identity of Pleurothallis luctuosa, its taxonomic history and geographic distribution are discussed, and the species is described and illustrated. A new species from Costa Rica, P. neglecta, is described and illustrated. Pleurothallis neglecta is compared with P. luctuosa, from which it differs by the distinct conduplicate leaves, different color of the flowers, triangular and smaller lip, falcate, erose petals, and the callus formed by two conspicuous, densely papillose keels.